Tuberculosis: new treatments in evolution - Gillespie, Stephen (Henry Stewart Talks, 2014)
Tuberculosis history, The streptomycin trial, Headlines in tuberculosis drug development, Standard treatment for drug-sensitive TB – Toxicity, Treatment duration, Challenges in TB treatment, Some examples of drugs in development, New trials to shorten treatment for TB, Fluoroquinolones for TB, Johns Hopkins study, REMoxTB study objective, Overview of TB microbiology protocols – Safety, Gatifloxacin project: phase III, More TB drug development approaches, New combination regimen studies, MAM- multi arm multi stage, Developing new treatments for MDR/XDRTB, Current WHO treatment for MDRTB, Using existing and repurposed drugs, New drugs for MDRTB (Delanamid, Bedaquinline), Drugs in development for MDR indication